Naphthalene tetracarboxydiimide-based n-type polymers with removable solubility via thermally cleavable side chains - Hillebrandt, Sabina; Adermann, Torben; Alt, Milan; Schinke, Janusz; Glaser, Tobias; Mankel, Eric; Hernandez-Sosa, Gerardo; Jaegermann, Wolfram; Lemmer, Uli; Pucci, Annemarie; Kowalsky, Wolfgang; Müllen, Klaus; et al. (ACS applied materials & interfaces, 2016)
Multilayer solution-processed devices in organic electronics show the tendency of intermixing of subsequently deposited layers. Here, we synthesize naphthalene tetracarboxydiimide (NDI)-based n-type semiconducting polymers with thermally cleavable side chains which upon removal render the polymer insoluble. Infrared and photoelectron spectroscopy were performed to investigate the pyrolysis process. Characterization of organic field-effect transistors provides insight into charge transport. After the pyrolysis homogeneous films could be produced which are insoluble in the primary solvent. By varying curing temperature and time we show that these process parameters govern the amount of side chains in the film and influence the device performance.
Gesehen am 13.05.2020